P53‐Based strategy to reduce hematological toxicity of chemotherapy: A proof of principle study. Issue 1 (18th September 2015) - Ha, Chul S.; Michalek, Joel E.; Elledge, Richard; Kelly, Kevin R.; Ganapathy, Suthakar; Su, Hang; Jenkins, Carol A.; Argiris, Athanassios; Swords, Ronan; Eng, Tony Y.; Karnad, Anand; Crownover, Richard L.; et al.
Abstract : p53 activation is a primary mechanism underlying pathological responses to DNA damaging agents such as chemotherapy and radiotherapy. Our recent animal studies showed that low dose arsenic (LDA)‐induced transient p53 inhibition selectively protected normal tissues from chemotherapy‐induced toxicity. Study objectives were to: 1) define the lowest safe dose of arsenic trioxide that transiently blocks p53 activation in patients and 2) assess the potential of LDA to decrease hematological toxicity from chemotherapy. Patients scheduled to receive minimum 4 cycles of myelosuppressive chemotherapy were eligible. For objective 1, dose escalation of LDA started at 0.005 mg/kg/day for 3 days. This dose satisfied objective 1 and was administered before chemotherapy cycles 2, 4, and 6 for objective 2. p53 level in peripheral lymphocytes was measured on day 1 of each cycle by ELISA assay. Chemotherapy cycles 1, 3, and 5 served as the baseline for the subsequent cycles of 2, 4, and 6 respectively. If p53 level for the subsequent cycle was lower (or higher) than the baseline cycle, p53 was defined as "suppressed" (or "activated") for the pair of cycles. Repeated measures linear models of CBC in terms of day, cycle, p53 activity and interaction terms were used. Twenty‐six patients treated with 3 week cycle regimens form the base of analyses. The mean white blood cell, hemoglobin and absolute neutrophil counts were significantly higher in the "suppressed" relative to the "activated" group. These data support the proof of principle that suppression of p53 could lead to protection of bone marrow in patients receiving chemotherapy. This trial is registered in ClinicalTrials.gov. Identifier: NCT01428128. Highlights: p53 activation is a major pathway for pathological response to DNA damaging agents. This p53 pathway is independent of tumor suppressor pathway of p53. Suppression of this pathway selectively protects normal tissue, not cancer, in vivo. We found arsenic dose that temporarily and reversibly suppresses this pathway in man. Successful suppression of p53 leads to protection of bone marrow from chemotherapy.